Composition effect on transport and microwave properties of YBCO thin films prepared by metalorganic chemical vapor deposition. Issue 12 (15th June 2022) - Chen, Tingyu; Xia, Yudong; Zhao, Ruipeng; Wu, Dong; Feng, Zhongpei; Yang, Jingting; Xin, Jijun; Wang, Wei; Jin, Kui; Tao, Bowan
Abstract: YBa2 Cu3 O7− δ (YBCO) thin films deposited on LaAlO3 single-crystal substrates have great potential for application in microwave field due to their low microwave surface resistance ( R s ). In order to prepare high-performance films and facilitate adjustment of experimental parameters, we designed novel metalorganic chemical vapor deposition system. This system adopts single liquid-source pulse feed that provides facile control over film composition through the adjustment of Y, Ba, and Cu ratios in precursors. Here, we thoroughly study influence of film composition on performance. By conducting energy-dispersive spectroscopy measurements, Y, Ba, and Cu composition ranges of 21–24%, 28–31%, and 46–54%, respectively, are found to optimize YBCO film transport and microwave properties. Composition affects purity of film phase which in turns determines film performance. To confirm this observation, we adjust ratio through input–output relationship to obtain film with composition ratio within abovementioned optimal range. Obtained YBCO film has critical current density of 2.8 MA/cm 2 at 77 K and 0 T and R s of 0.285 mΩ at 77 K and 10 GHz. The full width at half maximum of YBCO (005) peak and (103) plane, measured via X-ray diffraction, are 0.235° and 0.762°, respectively.